Addressing Gender in Climate-Smart Smallholder Agriculture - Bernier, Quinn; Franks P; Kristjanson, Patricia M.; Neufeldt, Henry; Otzelberger A; Foster K (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This brief focuses on the constraints that women face to more equitable participation in smallholder carbon and climatesmart initiatives. It highlights the important role that a flexible learning approach plays in advancing equity goals, and offers recommendations for concrete actions that can empower both women and men